IMPLEMENTASI PERATURAN DAERAH NO 10 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN / KEBERSIHAN DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Mutmainah '; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated problems of implementation of the Regional Regulation No. 10 of 2012 on Service Fees Waste / Hygiene where the amount of garbage strewn on the roadside, waste transportation process is not routinely done, and people who do not pay the levy cleanliness. The research problems are "How Pekanbaru Implementation Regional Regulation No. 10 of 2012 on retribution service fees Waste / Hygiene In New Simpang village". This study aims to determine how the implementation of Pekanbaru City Regional Regulation No. 10 Year 2012 on Waste Services retribution / Hygiene In the village new intersection Handsome District of the city of Pekanbaru. The sample in this study was 40 people. Data collection techniques are interview techniques, technical documentation, and technical questionnaires. The results of research by the author get, shows that the implementation of the Regional Regulation No. 10 of 2012 on Service Fees Waste / Hygiene In the village of Simpang Baru subdistrict Tampan Pekanbaru City Public opinion showed acquisition of the percentage of the choice of answers yes by 44% and the choice of answers not by 56% and opinions village, district and janitor shows the percentage gain on the choice of yes answers 52% and 48% did not answer. So Implementation Regional regulations No. 10 Year 2012 on waste levy of service / cleanliness in the village of Simpang Baru subdistrict handsome city of Pekanbaru by the overall respondents "Less Done" for the category that is done by 48% and by 52% in the category of less accomplished.So it concluded that the implementation of the Regional Regulation No. 10 of 2012 on Service Fees Waste / Hygiene In Simpang New Village District of Pekanbaru City Tampan public opinion and the district, village and the officer is Done.Keywords: Implementation of regional regulations, levies, waste services / cleanliness